The Spatialisation of the Future - Photis Lysandrou (City, University of London, City Political Economy Research Centre (CITYPERC), 2020)
This paper argues that the growth of the securities markets signifies the spatialisation of the future. The possibility of this spatialisation is explained in terms of Marx's commodity principle: it is because that principle has been expanded to encompass financial securities that the future now exists as a socially constructed space that parallels physical space. The necessity for this spatialisation is explained in terms of the financial pressures on the world's major public and private organisations: security-issuing governments and corporations need to use the future to escape financing constraints in the present just as security-buying institutional investors need to use the future to meet financial commitments in the present. As the precondition for the continuing growth in scale of the securities markets is compliance with the rules of commodity exchange, and as the 'liberal market economy' variety of capitalism is the only one in which this condition is unreservedly met, it follows that a key by-product of the increasing need to colonise the future to take the overspill of the pressures of the present will be an increasing convergence on this variety of capitalism.
Keywords: 330; Spatiality; Marx's commodity principle; varieties of capitalism; convergence of capitalisms